The EFFECT OF INFLATION ON THE NUMBER OF MEDIUM SMALL MICRO ENTERPRISES (MSMEs) 2016 - 2019 IN SUKOHARJO REGENCY - Sulistiyono Sulistiyono; Irma Nuriyaningsih; Frisca Nastasya Fiorentina; Gustita Putri (Management Department, Faculty of Economics and Business, Universitas Jambi, 2020)
Inflation, in brief, has the meaning of a tendency to increase the prices of goods and services in general and continuously. Inflation will affect macroeconomic activities, micro, and investment activities. This inflationary condition is also bothersome for producers as owners of Micro, Small, and Medium Enterprises (MSMEs). In 2016, the number of MSMEs in the Sukoharjo Regency was 11,187 and increased in 2019 by 20,030. However, the increase in the number of MSMEs is, in fact, inversely related to the decreasing inflation rate. In 2016 the inflation rate was 2.34%, and in 2019 the inflation rate was 2.13%. The sample used in this study were all MSMEs registered at the Industry and Trade Service (Disperindag) of Sukoharjo Regency in 2016-2019. the number of MSMEs in the Regency increased. In 2017 there were 19,804 units, then to 20,580 in 2018. The increase was 8,617 pieces per year. The results of the data analysis show that inflation has an effect on the number of MSME players in Sukoharjo Regency. This means that the higher the inflation rate, the number of Micro, Small, and Medium Enterprises players will decrease.